How to Derive a Formula of Arithmetic Series | Arithmetic Progression

Arithmetic Series

An $\textit{arithmetic series}$ is the sum of the terms of an arithmetic sequence.
For example:

  • $4, 7, 10, 13, \cdots,61$ is a finite arithmetic sequence.
  • $4+7+10+13+ \cdots +61$ is the corresponding arithmetic series.

If the first term is $u_{1}$ and the common difference is $d$, the terms are:
$$u_{1},u_{1}+d,u_{1}+2d,u_{1}+3d,\cdots$$
\( \begin{align} \displaystyle \require{AMSsymbols} \require{color}
u_{1} &= u_{1} \\
u_{2} &= u_{1} + d \\
u_{3} &= u_{1} + 2d \\
&\vdots \\
u_{n-2} &= u_{n}-2d \\
u_{n-1} &= u_{n}-d \\
u_{n} &= u_{n} \\
S_{n} &= u_{1} + (u_{1}+d) + (u_{1}+2d) + \cdots + (u_{n}-2d) + (u_{n}-d) + u_{n} \\
S_{n} &= u_{n} + (u_{n}-d) + (u_{n}-2d) + \cdots + (u_{1}+2d) + (u_{1}+d) + u_{1} \color{red}\text{ reversing} \\
2S_{n} &= \overbrace{(u_{1}+u_{n})+(u_{1}+u_{n})+(u_{1}+u_{n})+ \cdots + (u_{1}+u_{n})+(u_{1}+u_{n})+(u_{1}+u_{n})}^{n} \color{red}\text{ adding these}\\
2S_{n} &= n(u_{1}+u_{n}) \\
\therefore S_{n} &= \dfrac{n}{2}(u_{1}+u_{n}) \\
S_{n} &= \dfrac{n}{2}\Big[u_{1}+u_{1}+(n-1)d\Big] \ \color{red}u_{n}=u_{1}+(n-1)d\\
\therefore S_{n} &= \dfrac{n}{2}\Big[2u_{1}+(n-1)d\Big] \\
\end{align} \)

If we know the first term $u_{1}$, the common difference $d$ and the number of terms $n$ that we wish to add together, we can calculate the sum directly without adding up all the individual terms.

It is worthwhile also to note that $S_{n+1} = S_{n} + u_{n+1}$. This tells us that the next term in the series $S_{n+1}$ is the present sum, $S_{n}$, plus the next term in the sequence, $u_{n+1}$. This result is useful in spreadsheets where one column gives the sequence, and an adjacent column is used to give the series.

Example 1

Find the sum of $3+5+7+ \cdots$ to $60$ terms.

\( \begin{align} \displaystyle
u_{1} &= 3 \\
d &= 2 \\
d &= 60 \\
S_{60} &= \dfrac{60}{2}\left[2 \times 3 + (60-1) \times 2\right] \\
&= 3720
\end{align} \)

Example 2

Find the sum of $5+8+11+ \cdots +599$.

\( \begin{align} \displaystyle
u_{1} &= 5 \\
d &= 3 \\
u_{n} &= 599 \\
u_{1}+(n-1)d &= 599 \\
5 + (n-1) \times 3 &= 599 \\
(n-1) \times 3 &= 594 \\
n-1 &= 198 \\
n &= 199 \\
S_{n} &= \dfrac{n}{2}{(u_{1}+u_{n})} \\
&= \dfrac{199}{2}(5+599) \\
&= 60\ 098
\end{align} \)

Unlock your full learning potential—download our expertly crafted slide files for free and transform your self-study sessions!

Discover more enlightening videos by visiting our YouTube channel!

 

Algebra Algebraic Fractions Arc Binomial Expansion Capacity Common Difference Common Ratio Differentiation Double-Angle Formula Equation Exponent Exponential Function Factorise Functions Geometric Sequence Geometric Series Index Laws Inequality Integration Kinematics Length Conversion Logarithm Logarithmic Functions Mass Conversion Mathematical Induction Measurement Perfect Square Perimeter Prime Factorisation Probability Product Rule Proof Pythagoras Theorem Quadratic Quadratic Factorise Ratio Rational Functions Sequence Sketching Graphs Surds Time Transformation Trigonometric Functions Trigonometric Properties Volume




Related Articles

Responses

Your email address will not be published. Required fields are marked *